Riggia cryptocularis (Crustacea: Cymothoidae) parasitizing three fish species in a hydroelectric dam - M. S. Sampaio, Wagner; Belei, Frederico; Giongo , Patrícia; R. Ferreira , Sebastião; Fernandes , Anderson; M. Lopes, Denilce (Revista Saúde & Diversidade, 2017)
Introduction: Parasites play important roles in ecosystems, but can also create disturbances in the composition of host fauna in anthropogenic environments. Objective: Knowledge about these organisms can contribute to the conservation of diversity and environmental quality and prediction of disease risks. Methods: Parasites were collected from fish hosts in the Doce River (Claro River Basin, Middle Paranaíba) in areas of a small hydropower plant, following specific protocol and identified in the laboratory. Results: This is the first report of Riggia cryptocularis (Crustacea: Cymothoidae) parasitizing Hypostomus ancistroides, Leporinus friderici and Serrasalmus maculatus. Conclusion: The presence of this parasite in three fish species during the same sampling period and the severity of mutilation in the host suggest that the dam may favor a possible outbreak of the parasite R. cryptocularis due to changes introduced in the environment by the establishment of this type of project.